A Literature Review: Effectiveness of NSAIDs in Osteoarthritis Patients - Adrianto, Madyo; Anak Agung Pradnya Paramitha Vidiani; Puspitaningrum, Anisa Nova; Girsang, Valentina (STIKES Telogorejo Semarang, 2024)
Pain, stiffness, swelling, and decreased joint function are some of the clinical signs of osteoarthritis, a disease that affects numerous anatomical and physiological aspects of joint tissue, cartilage degradation, bone remodeling, and osteophyte development. This literature review's objective is to ascertain the efficacy of NSAIDs in osteoarthritis by searching for journals from PubMed.. The method used was to search for articles through pubmed using the keywords